Pengaruh Brand Image Dan Word Of Mouth Communication Pada Keputusan Pembelian Produk Susu Dancow Di Bandar Lampung - Yessy Dekasari (Universitas Mitra Indonesia, 2020)
AbstractMarketing activities is one of the factors that affect the progress of the company. The term Brand image is a representation of the overall perception of the brand and is shaped from the past information and experience of the brand. The market has widely available various types of mass produced goods, consequently consumers are faced with many product choices, one of which is Dancow milk that competes with other brands of milk. he results show that the brand image and word of mouth together affect the decision to purchase Dancow milk in Bandar Lampung. This is evidenced by the t test, where t arithmetic t table with t value of each variable x1 that is brand image (2,349 1,986) and variable x2 word od mouth (3,132 1,986) hence statistically that all independent variable (brand Image and word of mouth)Affect the decision to purchase Dancow milk in Bandar Lampung. Test R of R2 = 0,150 this means contribution of variable X brand image and word of mouth role in influencing every variable Y (decision of purchase) equal to 15,0%The conclusion in this research is that Dancow milk should maintain and improve existing Brand Image variables, with good brand image then consumers will recommend to the nearest person to buy Dancow milk.Keywords: Brand image, Word of mouth and Purchase decision